Modelling of the grafting of maleic anhydride onto polyethylene in an extruder - Machado, A. V. (2004)
Grafting of maleic anhydride onto polyethylene is studied both computationally and experimentally. The mathematical model involves coupling the reaction kinetics to the description of flow in a twin-screw extruder. The predictions match the experimental observations satisfactorily.